Analisis Penggunaan Multimedia Interaktif di Sekolah Menengah Kejuruan - SYAH, MAENUDDIN BUSTANIL (Peneliti.net, 2025)
Learning within Vocational Secondary Schools (SMK) encounters obstacles in enhancing the efficacy of educational practices that align with the requisites of the industry. The implementation of interactive multimedia emerges as a viable solution to augment both the effectiveness and academic performance of students enrolled in SMK. This research endeavor seeks to systematically evaluate the application of interactive multimedia in the educational framework of SMK, discern prevailing research trajectories, and assess the efficacy and ramifications of interactive multimedia utilization. The methodology employed is a Systematic Literature Review (SLR) utilizing purposive sampling, which entails the selection of articles from SINTA indexed journals published within the past five years (2020—2024). From a comprehensive pool of 70,035 articles identified, merely 6 fulfilled the predetermined inclusion and exclusion criteria. The findings revealed that interactive multimedia markedly enhanced conceptual understanding, technical competencies, student motivation, and overall student learning outcomes. The literature review corroborates that the employment of interactive multimedia in the educational practices of Vocational High Schools (SMK) is exceedingly effective and exerts a beneficial influence on students’ conceptual comprehension, practical skills, motivation, participation, and learning outcomes.